Innovative Solar Water Pump with Automatic Water Level Regulator for Efficiency Rice Field Irrigation - Saragi, Indah Revita; Zuhra, Cut Fatimah; Simanjuntak, Crystina; Amaturrahim, Suci Aisyah; Hamid, Muhammadin; Abdul Ara; M Tegar Aliyu Bangun; Gavrylla Gilbert Siregar; Rio Geby Sitompul; Martahan Dapot Rezeki Sitompul; Alya Nazwariva; Inri Antanya Eukasih Br Karo (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Nowadays, most of human activities are related to the use of technology. The invention of various innovative ideas that simplify human life is essential. One of the uses advancement technologies can applied in agricultural field, especially for irrigation processes since it becomes the critical step in agricultural activity since it ensures that plants receive an adequate water. Due to the importance of irrigation, this community service activity aimed to provide information on how to build a solar pump for irrigation purposes and implement an innovative solar water pump with automatic water level control to improve the efficiency of irrigation of rice fields in Bekiung Village. The system is designed using solar panels as the main energy source, minimizing dependence on conventional electricity and fossil fuels. With the integration of water level sensor and automatic control system, the pump is able to adjust the water supply in real-time based on the actual needs of rice plants. Field tests show that the system is able to provide water consistently and efficiently, reducing water and energy wastage. The implementation of this technology not only improves irrigation efficiency, but also supports environmentally friendly sustainable agriculture. The results of this study are expected to serve as a model for other villages facing similar challenges in irrigation water management.